2001
DOI: 10.1359/jbmr.2001.16.7.1363
|View full text |Cite
|
Sign up to set email alerts
|

Soy Intake and the Maintenance of Peak Bone Mass in Hong Kong Chinese Women

Abstract: Our previous study on bone health among premenopausal women showed that bone mass consolidation is attained by the early 30s, and small loss of spinal bone mineral density (SBMD) occurs soon after peak bone mass attainment. Recent interest has been shown in the potential beneficial effects of phytoestrogens on bone health. However, data are lacking, particularly in Asian women. This study aims to investigate the effect of soy isoflavones intake on the maintenance of peak bone mass in a cohort of 132 women aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 30 publications
0
40
0
2
Order By: Relevance
“…These results are consistent with those of Potter et al [33] who reported that in postmenopausal women supplemented with isoflavones (90 mg/day), BMD and BMC significantly increased in the lumbar spine. Moreover, epidemiological studies indicated that isoflavonecontaining soy intake had a positive effect on the reduction in spinal bone loss in perimenopausal women [34] . The femur and spine in the OVX rats had lower BMD and BMC values than those of the sham-operated rats, but administration of isoflavone extract was shown to prevent bone loss in the femur and lumbar spine [32] .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of Potter et al [33] who reported that in postmenopausal women supplemented with isoflavones (90 mg/day), BMD and BMC significantly increased in the lumbar spine. Moreover, epidemiological studies indicated that isoflavonecontaining soy intake had a positive effect on the reduction in spinal bone loss in perimenopausal women [34] . The femur and spine in the OVX rats had lower BMD and BMC values than those of the sham-operated rats, but administration of isoflavone extract was shown to prevent bone loss in the femur and lumbar spine [32] .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Hong Kong suggested that there are different effective dosages of soy intake in females aged 30-40 years compared to 60-year-old females, which indicates that older people might need more soy intake to maintain the lumbar BMD. 85 Studies also presented that SI had a comparable positive protective effect on bone loss among younger postmenopausal women who had last menstruation within 7.5 years. 86 Since there is a rapid bone loss period from 12 to 60 months after the last period, because of the acute loss of estrogen, SI have not shown significant effects in early postmenopausal women with higher estrogen levels.…”
Section: Study Populationmentioning
confidence: 94%
“…Recently, genistein has been demonstrated to have an anabolic effect on bone metabolism, suggesting its role in the prevention of osteoporosis. [10][11][12][13][14] Genistein has a stimulatory effect on bone formation and mineralization in tissue culture systems in vitro, [15][16][17] and it can stimulate protein synthesis in osteoblastic cells. [18][19][20] Moreover, genistein has been shown to inhibit osteoclastic bone resorption by preventing the formation and differentiation of osteoclast-like cells from bone marrow cells, 21,22) and the apoptosis of mature osteoclasts is induced by genistein through the Ca 2ϩ signaling mechanism.…”
mentioning
confidence: 99%